174 Total antibody deficiency in B cell sufficient mice enhances atherosclerosis. (6th June 2015) - Sage, Andrew; Murphy, Deirdre; Masters, Leanne; Kitt, Lauren; Finigan, Alison; Mallat, Ziad
Abstract : Background and aim: Extensive studies have revealed an important protective function for IgM antibodies from B1a cells in atherosclerosis, whereas the role of B2 cells and IgG antibodies is uncertain, with both pro- and anti-atherogenic actions reported. The aim of this study was to specifically target antibodies but not other B cell functions and determine the effect on mouse atherosclerosis. Methods: We created MB1-Cre x XBP1 fl/fl mice that have B cell specific deficiency in the unfolded protein response transcription factor XBP1, previously reported to result in a specific antibody secretion defect. Specific antibody responses were assessed by ELISA and ELISpot after immunisation with NP-chicken gamma globulin. Chimeric Ldlr -/– mice with bone marrow from MB1-Cre x XBP1 fl/fl or control mice were fed a western diet for 8 weeks. Results: B cell XBP1 deficiency led to significantly attenuated antibody secretion after NP-CGG immunisation. Analysis of ldlr –/– chimeric mice revealed enhanced atherosclerosis progression in MB1-Cre x XBP1 fl/fl recipients. These mice displayed severely attenuated serum IgM, IgG and IgE levels, but intact spleen, lymph node and peritoneal B cells. There were no differences in total cholesterol levels. Antibody deficiency was associated with enhanced pro-atherogenic Th1 CD4 + T cell immunity. Conclusions: Antibodies have an overall protective effect on atherosclerosis and B2 cell antibodies are not responsible for enhanced atherosclerosis in IgM-deficient mice. Other B cell functions may be pathogenic in atherosclerosis.